Outcomes of organ‐sparing surgery for adult testicular tumors: A systematic review of the literature. Issue 5 (23rd February 2021) - Ory, Jesse; Blankstein, Udi; Gonzalez, Daniel C.; Sathe, Aditya A.; White, Joshua T.; Delgado, Carlos; Reynolds, John; Jarvi, Keith; Ramasamy, Ranjith
Abstract: Objective: To perform a systematic review on the effects of testicular sparing surgery (TSS) on the oncological, functional, and hormonal outcomes of adults with testicular tumors. Methods: A literature search was performed after PROSPERO registration (CRD42020200842) and reported in compliance with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) methods. We conducted a systematic search of Medline (Ovid), Embase, Cochrane CENTRAL, CINAHL, Scopus, Web of Science, ClinicalTrials.gov, and the WHO/ICTRP from inception to November 20, 2020. Manuscripts and published abstracts were included if they involved testis‐sparing surgery (TSS) and contained data on any outcomes related to fertility, hormonal parameters, or oncological control, or if they evaluated surgical technique. Results: Our initial search yielded 3, 370 manuscripts, with 269 of these screened for full‐text eligibility. After our exclusion criteria were applied, 32 studies were included in the final analysis. Oncological outcomes were obtained from 12 studies (average follow‐up 57.8 months), functional data from 26 studies (average follow‐up 49.6 months), fertility information from 10 studies (average follow‐up 55.8 months), and data on nonpalpable tumors from 11 studies (average follow‐up 32.1 months). Oncological control appears to be excellent in studies that reported these outcomes. Presence of germ cell neoplasia in situ was controlled with adjuvant radiation in nearly all cases. Functional outcomes are also promising, as development of primary and compensated hypogonadism was rare. Semen parameters are poor preoperatively among men with benign and malignant testis tumors, with occasional decline after TSS. Frozen section analysis at the time of surgery appears to be very reliable, and the majority of nonpalpable tumors appear to be benign. Conclusions: TSS is a safe and efficacious technique with regards to oncological control and postoperative hormonal function based on retrospective, noncontrolled studies. TSS avoids unnecessary removal of benign testicular tissue, and should be given serious consideration in cases of nonpalpable, small tumors under 2 cm. In cases of malignancy, TSS can safely avoid anorchia in men with bilateral tumors and in men with solitary testicles. The use of the operating microscope, while theoretically promising, does not necessarily lead to better outcomes, however data are limited.